A Systematic Review of Strategic Management Principles and Practices in the Context of Nonprofit Organizations - Dian Ramadhani (Penelitian dan Pengembangan Ilmu, 2024)
Strategic management plays a crucial role in guiding nonprofit organizations towards success inachieving their unique missions and objectives. This article aims to conduct a systematic reviewof the principles and practices of strategic management relevant to the context of nonprofitorganizations. The review encompasses the definition of strategic management in nonprofitorganizations and the importance of its implementation. The research method employed is aliterature analysis from various sources relevant to this topic. The review findings reveal thesignificance of strategic human resources management, the application of vulnerability-basedconceptual models for risk management, the evolution of strategic management practices innonprofit organizations, the urgency of strategic performance measurement, the impact ofboard performance on organizational effectiveness, crisis communication and strategic riskmanagement, as well as strategic decision-making and control. The practical implications of thisreview provide valuable insights for nonprofit practitioners in developing and enhancing theirorganizational strategies, as well as guiding future research in this domain.